Prevalence of Exfoliative and Toxic Shock Syndrome Genes in Methicillin- Resistant Staphylococcus aureus Strains Isolated from Clinical Specimens - Omar B. Ahmed (Current Overview on Disease and Health Research Vol. 4, 2022)
The emergence of MRSA strains possessing virulence genes encoding such toxins as exfoliative toxins (ets), toxic shock syndrome toxin-1 (TSST-1), is worrying, especially in relation to the increasing frequency of nosocomial infections. The objectives of the present study are to determine antimicrobial susceptibility and the prevalence of genes encoding ets and tsst-1 in clinical MRSA isolates in tertiary care hospitals. A total of 315 S. aureus strains were randomly collected from different clinical samples and were tested for antimicrobial susceptibility for MRSA. All the MRSA strains were confirmed for mecA gene and analysed for their eta, etb and tst genes by PCR. The results showed that out of 315 investigated 31.2% were MRSA. The study showed that the resistance rates among MRSA isolates for Penicillin-G, oxacillin were 100% while for vancomycin and fosfomycin were 99% and 93% respectively. No resistance to linezolid, teicoplanin, tigecycline was detected in MRSA isolates. Among the MRSA isolates, 4% were positive for tst and 2% were positive for etb toxin gene, while none eta toxin genes were detected. It was concluded that the vancomycin, teicoplanin, tigecycline and linezolid are the drugs of choice for the treatment of MRSA infections, the rates of ets and tsst-1encoding genes among MRSA isolates were low regarding the global prevalence.